Determining the association between stress and periodontal disease: A pilot study - Alkesh S Shende; Anuradha G Bhatsange; Alka S Waghmare; Lalitha B Shiggaon; Vijay N Mehetre; Ekta P Meshram (Wolters Kluwer Medknow Publications, 2016)
Aim: To evaluate the relationship between stress and periodontal disease. Materials and Methods: This study included fifty chronic periodontitis subjects. The clinical parameters assessed for the full-mouth periodontal examination were as follows: Plaque index (PI), probing depth (PD), and clinical attachment level (CAL). The subjects were provided with a questionnaire for the assessment of stress based on the Zung's self-rating depression and anxiety scale, the scores of which were correlated with the periodontal findings. Results: The number of subjects showing depression and anxiety were significantly less and the severity of depression and anxiety was mild in them. The clinical parameters (PI, PD, CAL) showed no significant differences among the subjects with varying levels of stress. There was no statistical significance for stress to be contributing toward the periodontal disease. Conclusion: The present study showed no association between stress and periodontal disease, and future longitudinal studies directed at larger population, might yield conclusive results.